2023
DOI: 10.2215/cjn.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Markers of Ultra-Processed Food and Incident CKD

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Our study also identified exogenous metabolite catechol sulfate levels and the amino acid metabolite 3-methylglutaconate levels as risk factors for the onset of psoriasis. Catechol sulfate is recognized as one of the biomarkers for the intake of ultra-processed foods, with its metabolite levels significantly correlating with the consumption of such foods ( 48 ) The increased consumption of ultra-processed foods has been reported to elevate the risk of various diseases, including diabetes, depression, and cancer ( 63 65 ). Therefore, individuals with psoriasis should limit their intake of ultra-processed foods to prevent the potential risk increase associated with high levels of catechol sulfate metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also identified exogenous metabolite catechol sulfate levels and the amino acid metabolite 3-methylglutaconate levels as risk factors for the onset of psoriasis. Catechol sulfate is recognized as one of the biomarkers for the intake of ultra-processed foods, with its metabolite levels significantly correlating with the consumption of such foods ( 48 ) The increased consumption of ultra-processed foods has been reported to elevate the risk of various diseases, including diabetes, depression, and cancer ( 63 65 ). Therefore, individuals with psoriasis should limit their intake of ultra-processed foods to prevent the potential risk increase associated with high levels of catechol sulfate metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence from prospective cohorts indicates a significant correlation between elevated mannose levels and high risk of kidney failure requiring replacement therapy [ 19 ]. Concurrently, mannose has been employed as a biomarker to elucidate the observed association between the consumption of ultra-processed food and chronic kidney disease (CKD) [ 20 ]. These findings align with our own.…”
Section: Discussionmentioning
confidence: 99%
“…The study of 5alpha-androstan-3beta-17betadiol disulfate was limited to the field of Alzheimer's disease (AD) [34]. And elevated serum N2, N2-dimethylguanosine was used for chronic kidney disease (CKD) diagnosis [35]. Urinary excretion of N2,N2dimethylguanosine by adults was used for acute leukemia follow-up [36].…”
Section: Discussionmentioning
confidence: 99%